A late embryogenesis abundant protein GsPM30 interacts with a receptor like cytoplasmic kinase GsCBRLK and regulates environmental stress responses. (June 2019) - Sun, Mingzhe; Shen, Yang; Yin, Kuide; Guo, Yongxia; Cai, Xiaoxi; Yang, Junkai; Zhu, Yanming; Jia, Bowei; Sun, Xiaoli
Highlights: A Glycine soja receptor like kinase GsCBRLK interacts with a LEA protein GsPM30. The N-terminal variable domain of GsCBRLK is sufficient for GsPM30 interaction. GsCBRLK shows interaction specificity with group 3 LEA proteins. GsCBRLK and GsPM30 display overlapping subcellular localization and tissue expression. GsPM30 contributes to increased tolerance to salt and drought stresses. Abstract: A Glycine soja receptor like cytoplasmic kinase GsCBRLK was previously characterized as a positive regulator of salt tolerance. However, how GsCBRLK regulates stress responses remains obscure. Here, we report the interaction between GsCBRLK and a group 3 late embryogenesis abundant protein GsPM30, and suggest its role in stress responses. GsPM30 was found to physically associate with GsCBRLK through yeast two hybrid assays, which was verified by bimolecular fluorescence complementation analysis. Deletion analyses showed that the N-terminal variable domain of GsCBRLK was sufficient for GsPM30 interaction. Besides GsPM30, GsCBRLK could associate with several group 3 LEAs, of which the N-terminus sequences show high identity with GsPM30. Lower binding affinity or even no interaction was observed between GsCBRLK and other group 3 LEAs, which are less closely related to GsPM30. Furthermore, we observed that GsPM30 could localize surrounding the internal circumference of plant cells, as well as in cytoplasm and nucleus. In addition, GUS staining and quantitative real-time PCR results suggested the ubiquitous expression in different tissues and induced expression by NaCl and mannitol treatments for GsPM30 . Consistently, GsPM30 overexpression in Arabidopsis caused increased tolerance to high salinity and dehydration/water deficit at both the young and adult seedling stages. Our results demonstrated the interaction between GsCBRLK and LEAs, and revealed the positive role of GsPM30 in stress responses.